Вы находитесь на странице: 1из 7

Option 3

Chapter 1
3 3 3 3
Exercise 1.1 6 ⫺ + ⫺ + $ ; converges to 1
2 4 8 16
1 Converges to 0 2 Converges to 2 1 2 2 8
7 + + + + ; diverges by nth term divergence test
3 Converges to 0 4 Diverges 3 9 9 27 $
5 Converges to 0 6 Converges to 0 8 ⫺1 + 1 ⫺ 1 + 1 ⫺$ ; diverges by nth term divergence test
7 Diverges 8 Diverges 5 7 3 11
9 + + + + ; diverges by nth term divergence test
9 Converges to 2 10 Converges to 1 11 16 7 26 $
11 Diverges 12 Converges to 1 1 1 1 1 1
10 + 2 + 3 + 4 + $ ; converges to
13 Converges to 0 14 Converges to 1 e e e e e ⫺1
∫ xe dx = ⫺ e⫺x (x + 1) + C
⫺x
15 Converges to 1 16–18 Proof 11 a)
1 ∞
19 20 2 2
∫ xe
⫺x
2 b) dx = and therefore the series is convergent.
1
e
1
21 22 Converges to π 12 a) Divergent b) Convergent
2 1
23 ⫺1 24 ⫺ 13–14 Proof
3 ∞
1
1 1 15 For ∑ , lim an = 0 but it is a p-series with
25 26 n=1 n n→∞
6 3
1
28 ln ⎛ ⎞
a p= 艋 1 so the series diverges.
27 ln 2
⎝ b⎠ 2
16 Proof 17 Converges
29 1 30 Divergent
1 18 Diverges 19 Converges
31 32 π
2 20 Converges 21 Converges
1 22 Diverges 23 Diverges
33 34 Divergent
2
24 Diverges 25 Diverges
35 ln 2 36 2
26 Diverges 27 Converges
37 k
28 Diverges 29 Converges
38 a) Area increases without bound, i.e. infinite
30 Converges 31 Diverges
b) π units3
c) The area of the region is infinite; however, the volume of 32 5
10  016 1
the solid created by rotating the region about the x-axis is 33 a) S4 = ≈ 0.908   48; error <
finite. 11 025 81
b) S4 = 0.095  3083; error < 0.000 006
34 a) (n + 1)2 + 1
Chapter 2

1 π
b) ∫ dx = lim [arctan (x + 1)]1 = ⫺ arctan (2)
b

( x + 1) 2
+ 1 b→∞ 2
Exercise 2.1 1

= arctan ⎛ ⎞ ; since ∫
1 a) 8 b) ⫺1 c) 25 1 1
dx converges to
3 3 1 ⎝ 2⎠ (x + 1)2 + 1
1
2 a) b) c)
4 4 1+ x ∞
arctan ⎛ ⎞ , then ∑ 2
1 1
⎝ 2⎠ must also converge.
1
+
2
+
3
+
4
+ $ ; diverges by nth term n + 2n+2
3 35 Diverges
n =1
2 5 10 17
divergence test 36 a) 1.202 606 481 with error < 0.0061 b) 10 terms
3 3 3 37 11 terms
4 3+ + + + ; converges to 4
4 16 64 $ (⫺1)n+1

1 1 1
38 ∑ = 1 ⫺ + ⫺ + $ is conditionally convergent.
n =1 2n ⫺ 1
1 1 1 3 5 7
5 0 + ln + ln + ln + $ ; diverges by nth term divergence
2 3 4 39 Converges absolutely 40 Converges conditionally
test
41 Diverges 42 Converges conditionally
Answers

43 Converges absolutely 44 Converges absolutely 1 1


22 ⫺ <x<
1 1 1 1 1 1 1 2 2
45 1 + ⫺ + ⫺ + + ⫺ + $ ; the sum of this series (x ⫺ 1)3 (x ⫺ 1)4
3 2 5 4 7 9 8 23 (x ⫺ 1) e + (x ⫺ 1)2 e + e+ e
2 6
is 1. The terms of the alternating harmonic series are ∞
2 2x 3 2x 5
rearranged such that consecutive positive terms are added 24 ∑ x 2n⫺1 = 2 x + + +$
n =1 (2n ⫺ 1) 3 5
until the sum is greater than 1, then consecutive negative

terms are added until the sum is less than 1, and so on. Note
that the difference between the partial sums and 1 is less than
25 a) ∑ (⫺1) n
x 2n = 1 ⫺ x 2 + x 4 ⫺ x 6 + $
n=0
the last term used, so the series converges to 1. b) Proof c) Proof d) π ≈ 2.976; error < 0.142 86
46 7 terms 47 Proof e x + (⫺1)n e⫺x
26 a) f (x ) =
(n)
2
x2 x4
b) f (x ) = 1 + + +$
Chapter 3 2 24
f ⎛ ⎞≈
1 433
c) = 1.127  604  16
Exercise 3.1 ⎝ 2 ⎠ 384
1 R = 1; ⫺1 艋 x < 1 2 R = 1; 1 < x < 3 d) Error < 0.000 136
3 R = 2; 2 艋 x < 4 4 R = ∞; x ∈^ 27 ⫺1.59 < x < 1.59
5 R = 1; ⫺1 艋 x 艋 1 6 R = 1; 1 艋 x 艋 3 x n+1

x3 x4
28 xe = ∑ = x + x2 + + +$
x

7 R = 1; 0 < x < 2 8 R = 1; ⫺1 艋 x < 1 n=0 n ! 2! 3!


4 4 4 2 x 4 17 x 6 62 x 8
9 R = 0; x = 0 10 R = ; ⫺ 艋 x < 29 sec 2 x = 1 + x 2 + + + +
3 3 3 3 45 315 $
11 R = 4; ⫺4 < x < 4 12 R = 3; ⫺ 3 艋 x 艋 3 ∞
e 2
30 a) ∑ (x ⫺ 2)n
13 R = e; ⫺ e < x < e 14 R = 0; x = 4 n=0 n !

n (x )
3 2 n +1
1 1 ∞ ∞
x 6n+ 3
15 ⫺ < x < b) ∑ (⫺1) = ∑ (⫺1)n
k

k n=0 (2n + 1) ! n=0 (2n + 1) !
16 a) ∑ (⫺1) n
x n ; ⫺1 < x < 1 1 ∞
c) ⫺ ∑ (n + 1) nx n⫺1
n=0
2 n=0
1 1
b) A = , B= ∞
(⫺1)n

2 2 d) ∑ n + 1 (x ⫺ 1) n+ 4

c) ∑ x 2n ; ⫺ 1 < x < 1 n=0

n=0
31 a) 1 1
b) __
x4 x6 x 2n 3
17 a) e ⫺x 2
= 1⫺ x + ⫺ + $ + (⫺1)n
2
+$; R = ∞
2! 3! n!
⎛ x4 x6 x 2n+1 ⎞ Practice questions
∫e ∫ ⎜⎝1 ⫺ x
⫺x 2
b) dx = 2
+ ⫺ + $ + (⫺1)n +
2! 3! (2n + 1) n ! $⎟⎠ 1 ln (cos x ) ≈ ⫺
x2 x4

2 12
x3 x5 x7 x 2 n +1 x4 x4
=x− + − + … + (−1)n + …; 2 a) sin 2 x ≈ x 2 ⫺ b) cos 2 x ≈ 1 ⫺ x 2 +
3 ⋅1! 5 ⋅ 2 ! 7 ⋅ 3! (2n + 1)n !
3 3
radius of convergence is also R = ∞. x 3
1
1 1 1 1 5651 3 e x sin x ≈ x + x 2 +
c) ∫ e⫺x dx ≈ 1 ⫺ + ⫺ +
2
= ≈ 0.747 ; 3
3 10 42 216 7560 9x 2 9x 3
0
4 e ≈ 1 + 3x +
3x
+
1 2 2
error < a6 = = 0.000 75 < 0.001
11 ⋅ 5 ! x 2 5x 4
5 sec x ≈ 1 + +
x4 x6 1 3 2 5 2 24
18 a) x 2 ⫺ + b) x + x + x
3! 5! 3 15 x2 x3 x4
6 a) e ≈ 1 + x +
x
+ +
1 2 7 3 2! 3! 4 !
c) x ⫺ x + x x4
2 6 b) e x ≈ 1 + x 2 +
∞ 2!
19 ∑ nx n⫺1
for ⫺1 < x < 1
c) e x ≈ 1 + x +
3 x 2
+
7 x 3 25 x 4
+
n=0

x n+ 2 2 6 24
20 a) ∑ (⫺1)n!
n
b) Proof
7 ln(2 + 3x ) = ln 2 + x ⫺
3 ⎛ 3⎞ 2 x 2 ⎛ 3⎞ 3 x 3 ⎛ 3⎞ 4 x 4
+ ⫺ + ;
n=0
2 ⎝ 2⎠ 2 ⎝ 2⎠ 3 ⎝ 2⎠ 4 $
x3 x5 x7
21 a) sin x ≈ x ⫺ + ⫺
3! 5! 7 ! (⫺1)n 3n+1
R n (x ) = x n+1
⎛ π⎞ (n + 1) (2 + 3c)n+1
b) sin ⎝ ⎠ ≈ 0.258  819
12 x x2 x3 5x 4
⫺10
8 a) 4+x ≈ 2+ ⫺ + ⫺
c) Error < 1.4165 × 10 4 64 512 16  384
2
1 ⫺3
7 9 e e
x 5 ; since 29 < (4 + 0.1)
1
b) R 4 ( x ) = 9
2 then c) P2 (x ) = e e ⫺ (x ⫺ e)2 , which is a parabola with
256 (4 + x ) 2 2
vertex (e , e1 e ).
7
0 艋 R 4 (x ) 艋 (0.1)5 < 5.34 × 10⫺10 24 Diverges by comparison with the harmonic series
256 ⋅ 29
2n 2n 2n
9 2 terms needed; 0.996 195 1 1 1 1
25 a) S2n = ∑ = Sn + ∑ 艌 Sn + ∑ = Sn +
k =1 k k =n +1 k k =n +1 2k 2

(⫺1)n x 2n x4 x6
10 a) ∑ n!
= 1⫺ x2 + ⫺ +
2! 3! $
b) Proof
2n n n
26 a) S2n = ∑ uk = ∑ (u2 k⫺1 + u2 k ) = ∑ ⎛ ⫺ ⎞
3 1

n=0
1 23
⫺x 2 ⎝ + k⎠
b) ∫ 0 e dx ≈ k =1 k =1 k =1 2 k 1 2
30 n
4k ⫺1
e =∑
c) Error < k =1 2 k (2k + 1)
42
1 ∞ b) Divergent by limit comparison test
11 a) = ∑ (⫺1)n+1 x 2n⫺2
1+ x 2
n =1
27 a) Integral test for ∑ an : Let an = f (n) ,where f(x) is a
π continuous, positive and decreasing function for all
b) Proof c) Proof d)
4 x 艌 N and N is some positive integer. Then the series
∞ ∞
1
12 a)
1+ x
≈ 1 ⫺ x + x 2 ⫺ x 3 + $ and ∑ an and the integral ∫ f (x ) dx both diverge or both
n= N N

1 converge. That is, if the integral is finite then ∑ an is


≈ 1 + x + x2 + x3 + $
1⫺ x finite, and if the integral is infinite then ∑ an is infinite.
⫺3 4 b) Converges by integral test
b) +
x ⫺2 x ⫺3 x3 x5 x7
28 a) (i) sin x ≈ x ⫺ + ⫺
x +1 1 11x 49 x 2 179 x 3 3! 5! 7 !
c) 2 ≈ + + + +
1296 $
4
x ⫺ 5 x + 6 6 36 216 2 x x6
(ii) e x ≈ 1 + x 2 + +
1 2! 3!
13 a)
1⫺ x x2 5 3 41 5
∞ b) e sin x ≈ x + x + x
6 120
b) ∑ ⎡⎣⫺ (x + 1) n⫺1
⎤⎦ = ⫺1 ⫺ (x + 1) ⫺ (x + 1)2 ⫺ (x + 1)3 ⫺ $ , 2
c)
5
n =1
6
⫺2 < x < 0 x 2 x 3 2x 4
29 ln(1 + sin x ) ≈ x ⫺ + ⫺
2! 3! 4!
14 a) Series converges by the ratio test
b) Series converges by the integral test 30 Ratio test gives interval of convergence as ⫺1 艋 x < 1.
c) Series converges by the alternating series test 31 Proof

15
4

1 ⎛ sin x ⫺ x ⎞ = lim ⎛ cos x ⫺ 1 ⎞ =
32 lim ⎝
x x ⫺1 x →0 x sin x ⎠ x →0 ⎝ sin x + x cos x ⎠
16 a) Series converges by the ratio test ⎛ ⫺ sin x ⎞ =0
lim
x → 0 ⎝ 2 cos x ⫺ x sin x ⎠
b) Series diverges by the integral test
17 a) Proof b) k = ⫺
1 33 Proof
cos x 1
32 34 a) (i) y ′ = ; y ′′ = ⫺ ; ⫺
c) Proof d) 3.1550 1 + sin x 1 + sin x
cos x

x 4n + 2
y (3) = ⫺ ;
18 a) ∑ (−1) (1 + sin x )2
n
b) 0.3103
(2n + 1) !
n=0
⫺ sin x (1 + sin x )2 ⫺ 2 (1 + sin x ) cos 2 x
19 a) R = 1 b) 4 艋 x 艋 6 y (4) =
(1 + sin x )4
20 Converges by the alternating series test; sum ≈ 0.63 (ii) Proof

xn 1 1 1
b) (i) ln(1 ⫺ sin x ) = ln (1 + sin (⫺x )) = x ⫺ x 2 + x 3 ⫺ x 4 + $
21 a) ∑ (⫺1)n⫺1 b) Proof 2 6 12
n =1 n 1 1
(ii) ln(cos x ) = ⫺ x 2 ⫺ x 4 + $
22 a) Converges by comparison test 2 12
b) Converges by alternating series test 1 3
(iii) tan x = x + x + $
23 a) Proof 3
c) ⫺2
b) y 1
35 R =
4
(e , e 1 e )
36 a) (i) Converges by alternating series test
y=1 1 1 1
(ii) S4 = 1 ⫺ + ⫺ ≈ 0.841  468
3! 5! 7 !
x
(iii) Error < 0.000 002 76 = 2.76 × 10⫺6

3
Answers

x3 x5 x7
b) (i) sin x = x ⫺ + ⫺ + 52 p > 1
3! 5! 7 ! $
x 2n⫺1 53 a) ln 2 b) ⫺3
(ii) an = (⫺1)n⫺1 e x + (⫺1)n e⫺x
(2n ⫺ 1) ! 54 a) (i) f (x ) =
(n)
2
(iii) Proof
x2 x4
x2 x4 x6 (ii) f ( x ) = 1 + + +
(iv) cos x = 1 ⫺ + ⫺ + 4 $
2! 4! 6! $
2
1 ⎛ 1⎞ 1 1 433
37 a) b) 0 (iii) f ⎝ ⎠ ≈ 1 + + =
2 2 8 384 384
38 a) (i) Proof (iv) Error < 0.000 136
1 b) Series is convergent by integral test
(ii) Converse is not true; a counter example is ∑ 2
n ⎡ π π⎤
1
which is convergent but ∑ is not. 55 a) (i) Domain [⫺1, 1] , range ⎢⫺ , ⎥
n ⎣ 2 2⎦
b) (i) k > 1 (ii) k ⭐ 1 x3
(ii) arcsin x = x + +$
39 a) (i) Proof 6
12 × 32 × $ (n ⫺ 2)2 x2 x4
(ii) an = , for odd n 艌 3 b) cos(arcsin x ) = 1 ⫺ ⫺
n! 2 8
r
b) R = 1 ⎛ q ⎞ ⎛ q r (r ⫺ 1) q 2 4 ⎞
c) (i) p r ⎜1 + x 2 ⎟ = p r ⎜1 + r x 2 + x
c) π ≈ 3.139 ⎝ p ⎠ ⎝ p 2 p 2 ⎟⎠
1 1
40 a) lim an = b) N = 1501 (ii) p = 1, q = ⫺1, r = ; hence, the series in b) and c)
n→∞ 2 2
is (1 ⫺ x 2 )
1
2
41 ⫺1.59 < x < 1.59 since
(
cos (arcsin x ) = cos arccos 1 ⫺ x 2 = (1 ⫺ x 2 ) 2 . )
1

42 Convergent by comparison with geometric series ∑ 2 ⫺n

43 a) Proof b) Proof 56 a) 2 b) ⫺1 c) Proof


2 4
c) S = e ⫺1 57 a) (i) Proof (ii) Proof (iii) p = ,q=
3 3
44 a) Proof b) Proof b) Proof c) Proof
c) GDC value: ln (1.5) ≈ 0.405   465  1081 58 Series is convergent by the ratio test

x 3 3x 2 11 1
For x = 1.5 : ⫺ + 3x ⫺ = 0.416. 59 a) Proof b) 1.18 < ∑ < 1.22
3 2 6 n =1 n3
x 3
x 2
3x 5 1 60 a) 0
For x = 1.5 : ⫺ + ⫺ ⫺ = 0.406   25.
12 2 2 6 4x 1 1 2
b) f ′ (x ) = , f ′′ (x ) = ( )
2 , f ′′′ x =
The second approximation is nearer to the true value. 1⫺ x (1 ⫺ x ) (1 ⫺ x )3
1 ⎛ 1 + α 2n 2 ⎞ 1 1 1 2
45 a) (i) In = ln ⎜ c) ln 2 ≈ + + =
2 ⎝ 1 + n 2 ⎟⎠ 2 8 24 3
d) Error < 0.25
1
(ii) lim In = ln (α ) or lnα 2
2
n→∞ 2 e) Actual error = ln 2 ⫺ ≈ 0.026   48; upper bound for
3
b) ⫺2 error found in d) is much larger than the actual error, so
46 a) (i) 2 (ii) 2 2
the estimate of found in c) cannot be considered a
b) The argument is incorrect because the denominator is not 3
good estimate.
zero when x = 3.
1 1
47 a = 1, b = 1, c = , d = 0 61 a) b) ⫺2
2 2π
48 a) Convergent by comparison test, or limit comparison test 62 a) Proof
1 1 3 π π2 π4 π
b) (i) ⫺ (ii) b) Using x = : ln 2 ≈ + ; using x = :
2n 2 (n + 2) 4 3 4 18 972 4
49 ⫺1 艋 x < 1 π2 π
ln 2 ≈ + .
5 1 16 1536
50 a) ⫺ b) ⫺ 63 a) R = 3
8 2
1 1 b) Converges by limit comparison test (comparing to
51 a) A = , B = ⫺ ∞
1
4 4 convergent series ∑ 2 )
n=1 n
b) Sn = ⎛ ⫺
1 1 1 ⎞
64 a) Proof
4 ⎝ 3 4n + 3⎠ b) ln (1 + sin x ) = x ⫺
x2 x3 x4
+ ⫺ +
∞ 2 6 12 $
∑ ⎛⎝ 16r ⎞ = lim 1 ⎛ 1 ⫺ 1 ⎞ = 1 ; hence,
1
c)
r =1 +2
8 r ⫺ 3 ⎠ n→∞ 4 ⎝ 3 4n + 3⎠ 12 x2 x3 x4
c) ln (1 ⫺ sin x ) = ⫺x ⫺ ⫺ ⫺ ⫺
the series is convergent. 2 6 12 $

4
d) Proof 5 a)
e) 0
8
65 ⫺
315

66 Given ∑ an and an = f (n) , integral test can be applied if
n=1

f(x) is positive, continuous and decreasing for x > 1; ∑ n e⫺n
2

converges. n =1

67 8 + 17 (x ⫺ 1) + 16 (x ⫺ 1) + 7 (x ⫺ 1) + (x ⫺ 1)
2 3 4

68 a) 0 for ⫺1 ⭐ sin n ⭐ 1
π 2
b) c) 
2 5 5 5
d) 0 e) 0 f) ⫺1 b)
2
c)
2
1 d) Regardless of the initial value of the population, as time
69 a) Converges; geometric series with r = , so r < 1.
1.1 increases, the population stabilizes at 2 500.
b) Diverges by nth term divergence test
6 y = ⫺ x + tan x + 25
2
c) Converges by limit comparison test
d) Diverges by integral test 7 a) Proof
e) Converges; comparison test (compare to p-series with x +1
b) y =
p = 3) x ⫺1
π 2 (x ⫺ 12 ) π 4 (x ⫺ 12 )
2 4

70 a) sin (π x ) ≈ 1 ⫺ + −$ 8 (i) b (ii) d (iii) c (iv) a


b) 0.924 2! 4! 7x + 1
9 y=
7⫺x
1 1
10 a) ⫺
Chapter 4 3 (x ⫺ 2) 3 (x + 1)
b) proof
Exercise 4.1
1 (i) c (ii) a (iii) d
(iv) b 11 a) y = C (x 2 ⫺ 1) + 1
x
2 a) 2 x ⫺ y = C
2 2
b) y = dy ⎛ 2 x ⎞ 2x
1⫺ Cx b) + y= ; integrating factor is
1 y 1 dx ⎝ 1⫺ x 2⎠
1⫺ x2
c) ln ( y ⫺ 1) ⫺ ln y + C1 = ⫺ or = C2 e x 1
x y ⫺1 ; leads to same solution as in part a)
d) x = C1 sin y or y = arcsin (C2 x ) 1⫺ x2
C x2

x2
12 a) y = x 4 + 2 b) y = Ce 2 ⫺ 1
e) y = Ce 2 f) y 2 = 2 x 2 + 1 + C x
1 4
c) y = x + Cx d) y = xe + Ce cos x
cos x
y ⫺1 3
g) ln = ex + C h) x = y ln y ⫺ y + C
y +1 x3
e) y = xe + Ce
x3
f) y = x ln x + Cx
y +1 x +1 ⎛ 1⎞ ⎛ 1⎞
3 ∫ y
dy = ∫
x
dx ⇒ ∫ ⎜⎝1 + y ⎟⎠ dy = ∫ ⎝1 + x ⎠ dx 13 y = x csc x + C csc x

⇒ y + ln y = x + ln x + C 14 a)–c) Proof
x arcsin x 1
e y + ln y = e x + ln x +C ⇒ e ln y e y = e ln x e x e C ⇒ ye y = Axe x d) y = + +
2 2 1⫺ x2 1⫺ x2
4 y = ± 2 sin x + C
15 a)–b) Proof
The constant C cannot be completely arbitrary because c) y = tan x + C sec x
2 sin x + C 艌 0. If C < ⫺1, then 2 sin x + C will always 1 C
be negative, regardless of the value of x. If C > 1, then 16 y = x 2 +
3 x
2 sin x + C will always be positive. If ⫺1 艋 C 艋 1, then
1 2 1 10
whether 2 sin x + C is positive or negative will depend on 17 y = x ln x ⫺ x 2 +
the value of x. 3 9 9x
y⫺x
18 C =
( y + x )2
19 a) y = Cx + C b) y = Cx ⫺ x
2

c) y = Cx ⫺ x d) 2 x + 3xy + 3 y = C
3 3 2 3

2
x C
e) y 2 = ⫺ 2 f) y = x ln (Cxy )
2 x

5
Answers

20 a) Proof b) x 2 + 4 xy ⫺ 3 y 2 ⫺ 1 = 0 11 Proof
21 Proof 12 a) y ≈ 1.84
22 Proof
b) (i) y = 4 ⫺ x 2 (ii) y ≈ 1.77
y y 1
23 a) =C x b) = x c) 
y +1 y +1 2

c) xn yn
1.2 1.400
1.4 1.960
1.6 2.789
dy
1.8 4.110 Since is decreasing, the value of y is overestimated at
dx
each step.
d) xn approx. yn exact yn % error 1 1 1
13 a) a = , b = , c = ⫺
1.2 1.400 1.5 6. 6 2 2 2
1 1 1
b) (i) I = ln 1 + x + ln 1 + x − arctan x + k
2
1.4 1.960 2. 3 16.5 2 4 2
1.6 2.789 4.5 30.3 3π 3
(ii) C = ⫺ ln 2
1.8 4.110 9.5 54.3 8 4
24 y ≈ 1.5405 14 y ≈ 3.5
25 y ≈ 5.9584 15 a) Proof b) sec x
c) y = sin x + 2 cos x
26 y 2 = Cx 3 ⫺ x 2
27 16 a) Proof b) y 2 = 6 x 2 ln x + Cx 2
xn yn c) y = 6 x ln x + 4 x
2 2 2

1.1 4.2 17 y ≈ 2.14


3x 3 ⫺ x
1.2 4.425 43 18 a) Proof b) y =
3x 2 + 1
⫺ sin x
1.3 4.677 87 19 a) Proof b) e
1.4 4.959 04 c) y = ⫺ sin x ⫺ 1 ⫺ e sin x
1.5 5.270 81 20 a)–b)

28 a) Proof
b) y (1) ≈ 0.327  68
c) y (1) ≈ 0.348  678   4401
d) Actual value to 10 s.f. is y (1) ≈ 0.367  879   4412; using
more steps (and a smaller step size) gives a better
approximation.

Practice questions
1 a) y = (x + c) x 3 b) y = (x + 1) x 3

2 y= 2x 5 6x 2 3
+ +
5 5 5
1
3 y = Ce ⫺
x c) y = x ⫺1 + 4e
C sin x 21 a) (i) Proof
4 y= + ⫺ cos x
2 x 2 x 2 10 x 3 2 x 4
x x (ii) y = 2 + ⫺ ⫺ + +
C x3 16 x 3 1! 2! 3! 4! $
5 a) y = + b) y = + b) y (0.5) ≈ 2.55
x 4 x 4
c) y (0.5) ≈ 2.67
6 a) 6 b) 1 c) 2 d) 3 e) 4 f) 5
d) Approximation using Maclaurin series can be made
7 y = 8 sin x ⫺ 2
2

8x more accurate by computing more terms of the series;


8 a) y = ⫺2 x + 12 b) y = approximation using Euler’s method can be made more
x +1
9 y = tan x + sec x accurate by decreasing the step value.
y2
10 a) Proof b) 5 x =
x2
(
+ 1 or y = x 5 x ⫺ 1 )
6
3
1 1
22 yx 2 =
3
(1 + x 2 )2 +
3
23 a) Proof
y ⫺ 2⎞ 1 ⎛ ⎛ y ⫺ 2⎞ 2 ⎞
b) ln x ⫺ 1 = 3 arctan ⎛⎜ ⫺ ln 1 + +C
⎝ x ⫺ 1 ⎟⎠ 2 ⎜⎝ ⎜⎝ x ⫺ 1 ⎟⎠ ⎟⎠
1 2 ⎛ π⎞
24 a) 2 b) y = x arctan x + 1 ⫺
x ⎝ 4⎠
2
25 ln 2
3
26 a) (i) y (1.3) ≈ 2.14 (ii) Decrease the step size
b) y = x 2 + e1⫺x
2

x + 2⎞ ⎛
27 y = ⎛ + C⎞
1
ln (x + 2) +
⎝ x + 1⎠ ⎝ x+2 ⎠
28 y = x (x + 1) + C (x + 1)
2 2 2

E⎛ ⫺ t⎞
R
E RL t E
29 I = 1⫺ e L
; I = e ⫺
R ⎜⎝ ⎟⎠ R R
30 sec (xy ) = ⫺2 ln (cos x ) + C

⫺x